Computational studies of the structure and dynamics of packings of grain and bubbles - Delaney, Gary (Trinity College (Dublin, Ireland). School of Physics, 2006)
Since the dawn of civilization people have been intrigued by packing problems. They have a great significance in the practicalities of our everyday lives, with people always seeming to try to find more efficient ways of packing things together. Even though scientists have studied them for over 2,500 years, they are still prevalent today in almost every area of science. Much of the work that scientists have done on packing problems to date has been in considering sphere packings. These have been used widely to investigate the properties of granular materials and as simple models for everything from packings of atoms to packings of bubbles.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin